2019
DOI: 10.1002/gch2.201900013
|View full text |Cite
|
Sign up to set email alerts
|

Coated Urea Materials for Improving Yields, Profitability, and Nutrient Use Efficiencies of Aromatic Rice

Abstract: Intensive cultivation and introduction of input‐responsive high‐yielding varieties with application of major nutrients in rice–wheat rotation of Indo‐Gangetic plains (IGPs) lead to multiple nutrient deficiencies. A survey of Indian soils has shown that 40% are deficient in available zinc (Zn), 33% in sulfur (S), and 33% in boron (B). Studies have indicated that application of these nutrients with major nutrients can improve the crop productivity. Keeping the importance of aromatic rice in view, coated‐urea mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Babar et al [35] reported that the application of urea coated with Zn and copper showed a reduction in ammonia volatilization and maximized the N-uptake. Likewise, Shivay et al [36] applied urea coated with boron, sulfur, and Zn and reported an improvement in nutrient use efficiencies and harvest index. These urea-coated fertilizers showed an increase in grain yield of up to 13%, 25%, and 17.9% as compared to prilled urea.…”
Section: Discussionmentioning
confidence: 99%
“…Babar et al [35] reported that the application of urea coated with Zn and copper showed a reduction in ammonia volatilization and maximized the N-uptake. Likewise, Shivay et al [36] applied urea coated with boron, sulfur, and Zn and reported an improvement in nutrient use efficiencies and harvest index. These urea-coated fertilizers showed an increase in grain yield of up to 13%, 25%, and 17.9% as compared to prilled urea.…”
Section: Discussionmentioning
confidence: 99%
“…Most eggplant farmers apply only primarynutrient fertilizers which leads to low and variable crop yields and sub-optimal nutrient concentrations in the fruit. The ongoing use of primary-nutrient fertilizers combined with limited use of organic or micronutrient fertilizers has led to multi-nutrient de ciencies in the majority of soils in the Indian subcontinent [6][7] . Across India, approximately 89, 80 and 50 % of the arable soils are de cient in N, P and K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Across India, approximately 89, 80 and 50 % of the arable soils are de cient in N, P and K, respectively. Further, zinc (Zn), boron (B), iron (Fe), manganese (Mn), molybdenum (Mo), and copper (Cu) de ciencies have been reported in around 40, 33, 12, 5, 11 and 3 % of Indian soils, respectively [7][8][9] . Similarly, up to 51 % of the arable soils in China are de cient in Zn, with de ciencies in Mo, N, Mn, Cu and Fe in 47, 34.5, 21, 7 and 5 % of farmland soils, respectively, with large macronutrient (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations